Design and experiment of multi-row pneumatic precision metering device for rapeseed - Ibrahim, Elebaid Jabir; Liao, Qingxi; Wang, Lei; Liao, Yitao; Yao, Lu (International Journal of Agricultural and Biological Engineering, 2018)
The main objective of this study was to design a pneumatic disk with four-rows for planting rapeseed and to investigate its performance under several rotating speeds and vacuum pressure values. The effects of rotating speeds, vacuum pressure and rows on seed sucking and retaining were inspected. Six rotating speeds (5 r/min, 10 r/min, 15 r/min, 20 r/min, 25 r/min and 30 r/min) incorporated with the application of vacuum pressure were employed for detecting the optimum vacuum amount that was sufficient for seed sucking under each speed. These values of vacuum were found to be 1.1 kPa, 1.25 kPa, 1.35 kPa, 1.65 kPa, 1.8 kPa and 2.0 kPa, respectively. Moreover, a regression model was developed for predicting of vacuum pressure that corresponds with each rotating speed. Based on seed mass analysis, statistical differences were found at 5% significance under the influence of speeds and negative pressure and existed also between and within rows according to Duncan’s Test. The highest seed mass means of 3.17 g and 3.96 g were obtained by row 1 under the effects of speed and vacuum pressure, respectively, while the lowest means of 2.79 g and 3.05 g were attained by row 4. Due to the influence of rows, important differences were occurred between row 1 (closer to the center of rotation) and row 4 (farther one), particularly under high speeds (25 r/min and 30 r/min). Results concluded that, pneumatic disk with multiple-rows could be satisfactorily used for seed sowing with a little variation in seed amount between rows without any seed damage. The rows of hole farther from plate center of rotation were obviously influenced by angular velocity and vacuum amount rather than the closer ones.Keywords: precision seeder, metering device, performance, pneumatic, disk, multi-rows, rapeseedDOI: 10.25165/j.ijabe.20181105.3544Citation: Ibrahim E J, Liao Q X, Wang L, Liao Y T, Yao L. Design and experiment of multi-row pneumatic precision metering device for rapeseed. Int J Agric & Biol Eng, 2018; 11(5): 116–123.